(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Agriculture is the primary economic driver in every developed nation. Agriculture that uses smart technology encourages agricultural innovation, which helps solve economic problems. Smartphones and other Internet of Things devices make this possible. Farmers are able to monitor both their data and their activities. The Internet of Things is connected by embedded devices such as sensors, actuators, and others. The increased reliability of farmers will result from rapidly implementing Internet of Things technology in agriculture. The greater output of crops is required to feed a growing population. The optimal conditions for crop yields are moisture, temperature, and pH. The nutrients and moisture in the soil are essential for crop growth. It is imperative that crop production food levels be monitored more frequently. For this, a nutritional analysis is required. Take frequent readings of the soil's temperature, pH, and moisture content. Temperature, soil moisture, and microcontrollers control soil content, pH, and moisture. These findings are then periodically updated by cloud servers. Electrochemical sensors measure soil nutrients. The elements phosphorus, potassium, and nitrogen. Analysis and recommendations regarding the nutrients in live soil. This article provides information and recommendations regarding the pH of soil. Field maintenance and fertilization considering soil constituents. IOT esp8266 provides farmers with information.